Token-based robust deadlock-free dynamic reconfiguration protocol. (17th November 2014) - Kadhar, S. Mohiadeen Abdul; Revathi, T.
In network on chip (NoC), the network reconfiguration protocol is necessary to remap and reconnect the network paths so that the network remains to be connected. However, the reconfiguration process brings in deadlock problem. Only few existing works have considered the deadlock problem in NoC. Further, they paid no attention for reducing the packet loss rate. In this paper, we propose a token-based robust deadlock-free dynamic reconfiguration protocol. When a device observes topology changes or detects faulty nodes, it triggers the reconfiguration process and it becomes the reconfiguration controller (RC). Initially, HELLO message is transmitted by the reconfiguration controller to all devices for which they respond with a network status message. The RC constructs the new routing function based on the received network status messages. To synchronise the old and new routing functions, the reconfiguration controller distributes reconfiguration token in an ordered way. First, it distributes to the devices that surround the failed device and then to other devices. Every device holds the packet until it gets packet according to new routing function and then starts the transmission. By simulation, we show the efficacy of our reconfiguration protocol.